Features of Working on Breathing to Eliminate Tremolation in the Process of Learning to Sing - Zhang Ying (Музыкальное искусство и образование, 2020)
The article deals with the problem of eliminating one of the most common drawbacks in students’ singing – the presence of tremolation in the sound. It is noted that attention to this problem can be traced in the works of both Russian and Chinese scientists. At the same time, one of the ways to solve this problem is to develop proper singing breathing of future singers by introducing vocal exercises into the content of training, which are aimed at consciously controlling the singing apparatus when inhaling and exhaling. Analyzing the researchers’ views on breathing as the basis of singing intonation and their methodological recommendations, attention is drawn to the fact that in the works of Chinese scientists and practitioners, the main emphasis is on the use of special exercises, and the main thing is to develop the correct support for breathing. In the exercises recommended by Russian musicians-teachers, along with the technological component, the students’ attention is focused on the peculiarities of inhaling and exhaling, depending on the musical material being performed. One of the directions of vocal work to eliminate tremolation and even the possibility of its appearance, can be the acquirement of the correct breathing techniques by singers in the process of performing works that involve different ways of science of sounding.